Impact of the 2008 Crisis on Raw Materials and Food Products Prices in West-African Countries - Ndiaye, Madické Mbodj; Diop, Samba (DEMO, 2018)
The aim of this paper is to assess the impact of the 2008 crisis on the relationship between the raw materials and food products prices in some West African countries. We used the stability test of the estimated parameters for a regression model with a dummy variable representing the crisis. The results show that the index of raw materials has a significant and positive influence on the index of food products. However, the relationship is twice as high after the crisis. Then, the stability test confirmed the hypothesis that the crisis had an effect on the relationship. Finally, the test of significance of the dummy variable capturing the effect of the crisis once again justifies the impact of the 2008 crisis on the modelling of the price of food products and raw materials in these countries.(original abstract)